Comparison of craniofacial morphology in individuals with and without hypodontia with a special focus on the number of congenitally missing teeth - Fekonja, Anita; Čretnik, Andrej (Frontiers in Public Health, 2022)
Background Hypodontia might negatively affect dental function and esthetics, what might affect patients' self-esteem, communication behavior, professional performance and thus quality of life. The aim of this study was to estimate the influence of number of congenital missing teeth on dentofacial features. Methods Lateral cephalograms of 60 individuals with hypodontia (study group) and 40 individuals without hypodontia (control group) were analyzed. Patients in the study group were divided into two subgroups according to the number of missing teeth (group A with hypodontia 1 to 4 teeth and group B with hypodontia 5 or more teeth). Cephalometric data were compared among the study and control groups and statistically analyzed. Results The results in the present study revealed a significantly shorter and more retrognathic maxilla, more prognathic chin position, more retruded incisors in both jaws, large interincisal angle, straighter facial convexity as well as more retruded upper and lower lips in the group B compared with the control group. In the group A only chin position was significantly more prognathic compared with the control group. Conclusions According to the results of present study impact of hypodontia on the craniofacial morphology and consequently on facial esthetics was found statistically significantly greater in patients with 5 or more congenitally missing teeth.